Preferences and Decisions Models and Applications - Greco, Salvatore.; Marques Pereira, Ricardo Alberto.; Squillante, Massimo.; Yager, Ronald R.; Kacprzyk, Janusz. (Studies in Fuzziness and Soft Computing,, 2010)
This volume draws mostly on papers presented at the TRENTO 2009 international workshop on Preferences and Decisions, jointly organized by the University of Trento and the University of Sannio at Benevento (Italy). Since its first edition in 1997, the renowned international workshop series TRENTO aims at providing an informal but effective opportunity for sharing and discussing the recent research developments in the field of preference modeling and decision theory, bringing together some of the worlds leading experts in this active interdisciplinary area of research. In particular, the scope of the international workshop TRENTO 2009 covered a wide range of topics, such as preference representation and rationality, machine intelligence and automation in decision making, uncertainty modeling, probabilistic and possibilistic decision models, cooperative game theory and coalition formation, aggregation functions and multicriteria decision making, fuzzy set theory and fuzzy logic for decision making, algebraic structures, quantum dynamics, complex network models and negotiation, interactive dynamics and consensus reaching in multiagent decisions, optimization and operational research for decision making. The contributes have been proposed by authors that are among the most recognized scientists in the respective research domains. This volume also provides an opportunity, to colleagues and friends of Mario Fedrizzi, Benedetto Matarazzo, and Aldo Ventre, for celebrating and thanking them for their continuing and stimulating scientific work.